Analiza statystyczna zawartości azotu ogólnego w złożu oczyszczalni hydrofitowej w Małyszynie = Statistical analysis of total nitrogen in the soil of constructed wetland in Małyszyn - Jakubaszek, Anita; Wojciech, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Removal of nitrogen from constructed wetlands depends on many physic-chemical and biochemical conditions, deposit and environmental factors. The paper contains the results of statistical analysis the accumulation of total nitrogen in the soil. The results of the research have indicated that the highest content of nitrogen was observed in the surface layer of the soil at a depth of up to 20 cm. The content of total nitrogen has dropped with the penetration depth and towards the sewage flow from the constructed wetland.
Keywords: oczyszczanie ścieków; oczyszczalnie hydrofitowe; wastewater treatment; constructed wetlands